An endless continuum : humankind´s unending journey in kinnell´s the book of nightmares = Análisis del poemario The Book of Nightmares de Galway Kinnell - Quiros García, Elizabeth (2020)
This study presents an analysis, from a mythical and archetypical stance, of the archetype of the hero's journey in Galway Kinnell's The book of nightmares. Hence, the scholarly contributions of Carl Jung, Joseph Campbell and Octavio Paz will be mainly utilized to demonstrate how the three stages of the archetype are met : separation or departure, trials and victories of initiation, and return or reintegration with society.
Este trabajo de investigación se basa en un análisis del poemario The book of nightmares de Galway Kinnellutilizando como base teórica el enfoque mítico. Con este fin, se utilizará el aporte de Carl Jung, Joseph Campbell y Octavio Paz, principalmente, para demostrar como el yo lírico alcanza los diferentes estadios del monomito: separación, iniciación y sus pruebas y victorias, y el regreso o reintegración a la sociedad.
En Revista Intersedes, vol. 21, no 44, (Agosto-Diciembre 2020)
Descripción basada en el contenido visto el 19 de mayo, 2025
También disponible en formato HTML